Surface recombination analysis in silicon-heterojunction solar cells - Barrio, Rocío; Gandía, J. Javier; Cárabe, Julio; González, Nieves; Torres, Ignacio; Muñoz, David; Voz, Cristobal (My University, 2024)
The origin of this work is the understanding of the correlation observed between efficiency and emitter-deposition temperature in single silicon-heterojunction solar cells prepared by depositing an n-doped hydrogenated-amorphous-silicon thin film onto a p-type crystalline-silicon wafer. In order to interpret these results, surface-recombination velocities have been determined by two methods, i.e. by fitting the current–voltage characteristics to a theoretical model and by means of the Quasi-Steady-State Photoconductance Technique (QSSPC). In addition, effective diffusion lengths have been estimated from internal quantum efficiencies. The analysis of these data has led to conclude that the performance of the cells studied is limited by back-surface recombination rather than by front-heterojunction quality. A 12%-efficient cell has been prepared by combining optimum emitter-deposition conditions with back-surface-field (BSF) formation by vacuum annealing of the back aluminium contact. This result has been achieved without using any transparent conductive oxide.
Keywords: Silicon; PECVD; Amorphous; Heterojunction